Trading Roles : Gender, Ethnicity, and the Urban Economy in Colonial Potosí - Mangan, Jane E., 1969- (Book collections on Project MUSE., 2005)
A social history of trade in a colonial city in Peru, arguing that markets, stores, & taverns were important sites of cultural creation and showing how the gender and ethnic identities of participants affected how they adapted to the market economy.